Characteristics Of Patients With Deep Vein Thrombosis At Ibnu Sina Hospital Makassar During The Period 2023-2024 - Alya Anggriani; Reeny Purnamasari Juhamran; Tirta Swarga; Berry Erida Hasbi; Darariani Iskandar (Universitas Muhammadiyah Malang, 2025)
Introduction: Deep vein thrombosis (DVT) s the formation of blood clots in deep veins, commonly in the lower extremities. According to Virchow’s triad, blood flow stasis, hypercoagulability, and vascular damage contribute to its occurrence. This study aims to determine the characteristics of DVT patients at Ibnu Sina Hospital in Makassar during the period 2023–2024. Methods: A descriptive design with a mixed method (medical records and interviews) conducted at Ibnu Sina Hospital, Makassar, during the period 2023–2024. Used was total sampling of patients diagnosed with DVT. Data were processed using Microsoft Excel to produce frequency distributions and percentages. The Results: Most patients were aged 61–70 years (41%) and male (65%). The most common risk factors were prolonged bed rest (72%) due to stroke, femur fracture, heart failure, type 2 diabetes mellitus, acute renal failure, and osteoarthritis, followed by malignancy (24%) including breast, cervical, liver, and colorectal cancer. No patients with a history of DVT were found. The most common clinical symptom was leg swelling (47%). Conclusion: DVT at Ibnu Sina Hospital in Makassar was more common in the elderly, males, with prolonged bed rest as the main risk factor and malignancy as the second factor. Therefore, early mobilization, monitoring of risk factors, and more complete medical record keeping are necessary for the prevention of DVT.